Super-hydrophilic hydrotalcite-like modified alkaline water electrolysis composite diaphragm as well as preparation method and application thereof

By forming a hydrotalcite-like structure and nanoflower ball structure on the substrate surface of the alkaline water electrolytic composite separator, and performing hole filling and hydrophilic composite layer construction, the problems of high surface resistance, low wettability and poor gas barrier of the separator are solved, and super hydrophilicity and high-efficiency electrolytic hydrogen production are achieved.

CN119685878APending Publication Date: 2025-03-25SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411856290.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic separators have high surface resistance, low wettability and poor gas barrier properties during the electrolytic hydrogen production process, resulting in low electrolytic efficiency and safety hazards.

Method used

By forming an array-like bulk hydrotalcite structure on the substrate surface of the alkaline water electrolytic composite separator, and growing nanoflower ball structures on its edges, the hydrophilic composite layer is built with nickel-iron bimetallic hydroxide for pore filling and gradient construction, improving the hydrophilicity and gas barrier properties of the separator.

Benefits of technology

The super hydrophilicity of the diaphragm is achieved, the plane resistance is significantly reduced, the gas barrier performance and mechanical stability are improved, and the efficiency and safety of hydrogen production by electrolyzing water are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685878A_ABST
    Figure CN119685878A_ABST
Patent Text Reader

Abstract

The invention relates to a super-hydrophilic hydrotalcite-like modified alkaline water electrolysis composite diaphragm and a preparation method and application thereof, the super-hydrophilic hydrotalcite-like modified alkaline water electrolysis composite diaphragm comprises a base material, an array-shaped bulk phase hydrotalcite-like structure is formed on the surface of the base material, and a nano flower ball structure is grown on the edge of the hydrotalcite-like structure. According to the invention, the aperture of the diaphragm is locally filled with the hydrophilic inorganic filler or organic polymer, so that the aperture distribution of the diaphragm is adjusted, the macropore proportion is reduced, and the effect of reducing gas penetration is achieved. Hydrophilic inorganic filler is adopted to generate nano-particles in longitudinal gradient morphology distribution on the surface of the diaphragm in situ, and the surface energy of the diaphragm is increased through regulation and control of a surface nano-microstructure, so that the diaphragm has super-hydrophilicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of alkaline water electrolysis hydrogen production technology, and in particular to a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is a carrier of energy storage and transfer with abundant reserves, high calorific value and green environmental protection. The development and utilization of hydrogen energy has great strategic significance for adjusting my country's energy structure and ensuring energy security. With the development of renewable energy, the current hydrogen production by reforming fossil energy has been gradually replaced by water electrolysis hydrogen production technology. In the field of water electrolysis hydrogen production, alkaline water electrolysis technology has the advantages of low investment cost and simple operation, making it the most mature. However, alkaline water electrolysis technology consumes a lot of energy, and the electrolysis efficiency is usually 60% to 70%. The high electrolysis overpotential and large ohmic loss of the electrolyzer are the main reasons for the low energy efficiency of water electrolysis. The alkaline water electrolysis system also needs to strictly control the partial pressure balance of hydrogen and oxygen to prevent the occurrence of safety accidents such as hydrogen and oxygen mixing reaching the explosion limit.

[0003] From the analysis of the energy consumption structure of the alkaline water electrolysis system, it can be seen that the efficiency loss mainly comes from: (1) the overpotential loss of the electrode; (2) the ohmic loss caused by the diaphragm; (3) the external ohmic loss of the circuit and system. As the core material, the diaphragm is required to have low surface resistance, good wettability and gas barrier properties. Compared with traditional diaphragms, composite diaphragms combine the advantages of polymers and porous ceramics and have good mechanical stability, flexibility and wettability. However, the various properties of composite diaphragms still need to be improved, mainly including the following problems: (1) The large surface resistance and thick diaphragm (usually >500μm) lead to a large electrode spacing and a long ion migration distance, resulting in low conductivity; (2) Poor wettability. The surface of the diaphragm contains a dense polymer layer, which increases the hydrophobicity of the diaphragm. The hydrophobic surface causes bubble desorption and increases the ohmic resistance between the diaphragm and the electrode; (3) Poor gas barrier properties. The composite diaphragm has a high proportion of 1μm macropores, which is prone to gas product crossover, causing safety concerns.

[0004] In response to the above problems, existing composite membrane modification methods mainly focus on improving the wettability of the membrane. Improving the wettability of the membrane can reduce the precipitation of bubbles at the three-phase interface and accelerate the transmission of the electrolyte, thereby reducing the membrane surface resistance, ohmic loss and system energy consumption. However, the existing hydrophilic modification method has limited effect on improving the membrane wettability and cannot further inhibit the precipitation of bubbles at the interface, so the performance improvement is limited.

[0005] Chinese invention patent application number CN114351186A discloses a method for hydrophilic modification of a diaphragm for water electrolysis, a hydrophilic diaphragm and its application, which solves the problem of gas penetration through the diaphragm by preparing a hydrophilic oxide film on the surface of the diaphragm after alkaline washing pretreatment and introducing nanoparticles with catalytic activity to enhance the hydrophilicity of the diaphragm. However, the average water contact angle of the diaphragm mentioned in this patent is 60 degrees and the wetting time is 0.5s, so the wetting performance of the diaphragm needs to be further improved.

[0006] Chinese invention patent application number CN117089887A discloses a super hydrophilic membrane for hydrogen production by water electrolysis and a preparation method thereof, which reduces the surface resistance of the membrane and / or improves the hydrophilicity of the membrane by modifying a mixed solution of polyamide and carbon quantum dots in order to reduce the energy consumption of hydrogen production by alkaline water electrolysis. However, the average water contact angle of the modified membrane mentioned in this patent is 30 degrees, and the performance needs to be further improved, and the immersion time is not evaluated.

[0007] Chinese invention patent application number CN116334690A discloses a highly hydrophilic alkaline water electrolysis membrane and a preparation method thereof, which is prepared by preparing sulfonated polysulfone and nano-ceramic particles into a liquid membrane, and then preparing a solid membrane through a water coagulation bath. The hydrophilicity of the membrane is improved by controlling the amount of sulfonated polysulfone added, and a membrane with low resistance and good gas barrier properties is prepared. However, the average water contact angle of the modified membrane mentioned in this patent is 0 to 80 degrees, and the immersion time is not evaluated. Summary of the invention

[0008] The purpose of the present invention is to provide a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm and its preparation method and application, which proposes improvements on technical issues such as how to further reduce the water contact angle of the water electrolysis diaphragm, increase its wettability to reduce the surface resistance, while taking into account the gas barrier performance of the diaphragm and ensuring good mechanical stability, thermal stability and chemical stability of the diaphragm.

[0009] The present invention is implemented in this way:

[0010] A super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm comprises: a substrate, the surface of which is formed with an array of bulk hydrotalcite-like structures, and nano flower ball structures are grown on the edges of the hydrotalcite-like structures.

[0011] Preferably, the hydrotalcite-like structure comprises nickel-iron bimetallic layered hydroxide, and the hydrotalcite-like structure fills the pores of the substrate.

[0012] Preferably, the substrate comprises one or more of polyphenylene sulfide fabric, polyphenylene sulfide non-woven fabric, and an inorganic-organic composite substrate containing nano-ceramic fillers.

[0013] The present invention is implemented like this:

[0014] A method for preparing a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm comprises: immersing a substrate in a nickel-iron bimetallic salt solution and a potassium hydroxide solution in sequence; washing the surface of the substrate and drying it naturally; and drying to obtain the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm.

[0015] Preferably, the nickel-iron bimetallic salt solution includes one or more of nitrates and sulfates of nickel metal and one or more of nitrates and sulfates of iron metal.

[0016] Preferably, the molar ratio of Ni to Fe in the nickel-iron bimetallic salt solution is 1:(0.5 to 2).

[0017] Preferably, the immersing step and the rinsing and air-drying step are repeated 1 to 15 times in sequence.

[0018] Preferably, the immersion time in the nickel-iron bimetallic salt solution is 1 min to 10 min, and the immersion time in the potassium hydroxide solution is 1 min to 10 min.

[0019] Preferably, the drying temperature is 60°C to 100°C.

[0020] The present invention is also implemented like this:

[0021] An electrochemical energy device comprises: the above-mentioned super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm as its diaphragm.

[0022] Preferably, the electrochemical energy device is a water electrolysis hydrogen production device.

[0023] The present invention adopts pore filling, i.e., using hydrophilic inorganic fillers or organic polymers to partially fill the pore size of the diaphragm to adjust the pore size distribution of the diaphragm and reduce the proportion of large pores to achieve the effect of reducing gas penetration. The gradient construction of the hydrophilic composite layer is to use hydrophilic inorganic fillers to in-situ generate nanoparticles with a longitudinal gradient morphology distribution on the surface of the diaphragm, and increase the surface energy of the diaphragm by regulating the surface nano-microstructure, so that the diaphragm has super-hydrophilicity. In general, the beneficial effects achieved by the present invention are as follows:

[0024] (1) Good gas barrier properties: The present invention adopts a pore filling method to effectively control the pore size of the diaphragm, reduce the proportion of large pores, thereby increasing the bubble point pressure of the diaphragm and reducing hydrogen permeation.

[0025] (2) Super-hydrophilicity and low surface resistance: The present invention achieves super-hydrophilicity of the composite membrane by regulating the nanostructure of the membrane surface and adopting the strategy of “gradient construction of surface hydrophilic composite layer”, which greatly reduces the wetting time of the membrane, thereby inhibiting the precipitation of bubbles at the three-phase interface, reducing ohmic loss, and improving the water electrolysis efficiency of the system.

[0026] (3) Catalytic effect: The composite diaphragm of the present invention has a certain catalytic effect, which can reduce the overpotential of the anode or cathode, thereby reducing the cell pressure and improving efficiency.

[0027] (4) Simple operation and easy scalability: The materials of the present invention are widely available and do not use precious metals. The operation is simple and the cost is extremely low, which has good potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a schematic diagram showing the composite diaphragm structure of the present invention;

[0029] Figure 2 The scanning electron microscope photographs show the surface (a) and cross section (b) of the composite diaphragm of Example 1 and a partial enlargement of the hydrophilic composite layer (c);

[0030] Figure 3 is a graph showing the relationship between the water contact angle and wetting time of different membranes;

[0031] Figure 4 It is a curve graph showing the degree of polarization of water electrolysis with different membranes. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] The first embodiment of the present invention provides a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm, and the diaphragm may have the following characteristics:

[0035] The thickness is 350±20μm, preferably 330μm, 335μm, 340μm, 345μm, 350μm, 355μm, 360μm, 365μm, or 370μm; the bubble point pressure is 2.0bar to 5.5bar, preferably 2bar, 2.1bar, 2.2bar, 2.3bar, 2.4bar, 2.5bar, 2.6bar, 2.7bar, 2.8bar, 2.9bar, 3bar, 3.1bar, 3.2bar ar, 3.3bar, 3.4bar, 3.5bar, 3.6bar, 3.7bar, 3.8bar, 3.9bar, 4bar, 4.1bar, 4.2bar, 4.3bar, 4.4bar, 4.4b ar, 4.5bar, 4.6bar, 4.7bar, 4.8bar, 4.9bar, 5bar, 5.1bar, 5.2bar, 5.3bar, 5.4bar, or 5.5bar; surface resistance is 0.2Ω / cm 2 To 0.6Ω / cm 2 , preferably 0.2Ω / cm 2 , 0.3Ω / cm 2 , 0.4Ω / cm 2 , 0.5Ω / cm 2 , or 0.6Ω / cm 2 ; porosity is 50±10%, preferably 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, or 60%; average pore size is 80nm to 150nm, preferably 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, or 150nm; water contact The angle is ≤80 degrees, preferably 20 to 80 degrees, and more preferably 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80 degrees; the immersion time is ≤12s, preferably 0.1s, 0.2s, 0.3s, 0.4s, 0.5s, 0.6s, 0.7s, 0.8s, 0.9s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, or 12s.

[0036] Based on the above characteristics, the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite membrane proposed in the first embodiment can be used as a membrane of an electrochemical energy device, and the electrochemical energy device can be a water electrolysis hydrogen production device.

[0037] like Figure 1As shown, the diaphragm comprises: a substrate (1), the surface of the substrate (1) is formed with an array of bulk hydrotalcite-like structures (2), and nano flower ball structures are grown on the edges of the hydrotalcite-like structures (2).

[0038] The substrate may include one or more of polyphenylene sulfide fabric, polyphenylene sulfide non-woven fabric, and an inorganic-organic composite substrate containing nano-ceramic fillers. The inorganic-organic composite substrate containing nano-ceramic fillers may include nano-ceramic fillers as inorganic sources and organic polymers as organic sources; the nano-ceramic fillers may include one or more of zirconium oxide, titanium oxide, and cerium oxide; the organic polymer may include polyolefins, and the polyolefins preferably include one or more of polyethylene and polypropylene. The hydrotalcite-like structure (2) may include nickel-iron bimetallic layered hydroxide, and the hydrotalcite-like structure (2) may further fill the pores of the substrate (1).

[0039] The second embodiment of the present invention proposes a method for preparing a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite membrane, which can be used to prepare the composite membrane mentioned in the first embodiment, and can also be used to prepare other composite membranes not mentioned; that is, the composite membrane mentioned in the first embodiment should not be limited by the content mentioned in the second embodiment.

[0040] The preparation method of the second embodiment is carried out as follows:

[0041] First, a substrate is immersed in a nickel-iron bimetallic salt solution and a potassium hydroxide solution in sequence. The technical solution of the substrate can refer to the first embodiment and will not be repeated here. The nickel-iron bimetallic salt solution may include one or more of the nitrates and sulfates of nickel metal and one or more of the nitrates and sulfates of iron metal. In addition, the molar ratio of Ni to Fe in the nickel-iron bimetallic salt solution may be 1:(0.5 to 2), preferably 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, or 1:2.

[0042] The immersion time in the nickel-iron bimetallic salt solution can be 1 min to 10 min, preferably 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min; the immersion time in the potassium hydroxide solution can be 1 min to 10 min, preferably 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.

[0043] Next, rinse the substrate surface and let it dry naturally. Deionized water can be used for rinsing. In addition, immersing the substrate in the nickel-iron bimetallic salt solution and the potassium hydroxide solution in sequence and rinsing the substrate surface and letting it dry naturally can be repeated 1 to 15 times, preferably 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, or 15 times. It should be noted that when repeated multiple times, the time of immersing in the nickel-iron bimetallic salt solution refers to a single immersion time, and the time of immersing in the potassium hydroxide solution refers to a single immersion time.

[0044] Finally, the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite membrane is dried at a temperature of 60°C to 100°C, preferably 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C.

[0045] The following examples illustrate the present invention by way of example:

[0046] Example 1

[0047] This embodiment provides a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm, and the preparation process thereof is as follows:

[0048] Step 1: prepare a salt solution having a nickel-iron bimetallic, wherein the molar ratio of Ni to Fe is 1:1, and is recorded as solution A;

[0049] Step 2: Prepare a 1M potassium hydroxide solution, referred to as solution B;

[0050] Step 3: After the inorganic-organic composite substrate is immersed in solution A for 5 minutes, it is immediately immersed in solution B for 5 minutes, and then the inorganic-organic composite substrate is taken out from solution B, and the surface is rinsed with deionized water and dried naturally;

[0051] Step 4: After step 3 is repeated 10 times, the naturally dried inorganic-organic composite substrate is placed at 80° C. for drying to obtain a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm.

[0052] Example 2

[0053] The preparation process is the same as that of Example 1, except that in step 3, polyphenylene sulfide fabric is used instead of the inorganic-organic composite substrate.

[0054] Example 3

[0055] The preparation process is the same as that of Example 1, except that in step 3, polyphenylene sulfide non-woven fabric is used instead of the inorganic-organic composite substrate.

[0056] Example 4

[0057] This embodiment provides a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm, and the preparation process thereof is as follows:

[0058] Step 1: prepare a salt solution having a nickel-iron bimetallic, wherein the molar ratio of Ni to Fe is 1:1, which is recorded as solution A;

[0059] Step 2: Prepare a 0.2M potassium hydroxide solution, referred to as solution B;

[0060] Step 3: After the inorganic-organic composite substrate is immersed in solution A for 3 minutes, it is immediately immersed in solution B for 3 minutes, and then the inorganic-organic composite substrate is taken out from solution B, the surface is rinsed with deionized water and dried naturally;

[0061] Step 4: After step 3 is repeated 10 times, the dried inorganic-organic composite substrate is placed in an oven at 80° C. to obtain a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm.

[0062] Example 5

[0063] The preparation process was the same as that of Example 4, except that the inorganic-organic composite substrate was placed in solutions A and B for 1 min.

[0064] Example 6

[0065] The preparation process was the same as that of Example 4, except that the inorganic-organic composite substrate was placed in solutions A and B for 5 minutes.

[0066] Example 7

[0067] The preparation process was the same as in Example 4, except that step 3 was repeated once.

[0068] Example 8

[0069] The preparation process was the same as Example 4, except that step 3 was repeated 5 times.

[0070] Example 9

[0071] The preparation process is the same as that of Example 4, except that the drying temperature in step 4 is 60°C.

[0072] Example 10

[0073] The preparation process is the same as that of Example 4, except that the drying temperature in step 4 is 100°C.

[0074] Comparative Example 1

[0075] The preparation process is the same as that of Example 4, except that in step 3, only the inorganic-organic composite substrate is immersed in solution A.

[0076] Comparative Example 2

[0077] The preparation process is the same as that of Example 4, except that the drying temperature in step 4 is 120°C.

[0078] Test Example 1

[0079] In this test example, the surface and cross-section micromorphology of the composite diaphragm prepared in Example 1 were characterized by scanning electron microscopy (SEM). The results are as follows: Figure 2 shown.

[0080] from Figure 2 It can be seen that the surface of the hydrotalcite-modified composite diaphragm first generates an array of bulk hydrotalcite-like structures, and then continues to grow into nano-flower ball structures with the edges of the surface hydrotalcite-like nanosheets as sites. On the one hand, this nano-flower ball improves the surface roughness of the diaphragm and increases the surface energy, thereby making the composite diaphragm super-hydrophilic; on the other hand, the nano-flower ball, as the main catalytic site, can reduce the anode overpotential, thereby reducing the cell pressure and improving the system efficiency. In addition, this longitudinal gradient morphology modifies the surface structure of the diaphragm, reduces the proportion of macropores, and significantly increases the gas barrier properties.

[0081] Test Example 2

[0082] In this test example, the composite membranes prepared in Examples 2, 4, 7 and 8 and a commercial membrane (Zirfon UTP 500, purchased from Maxi New Energy Technology Co., Ltd.) were tested for water contact angle and wetting time. The experimental results are shown in Figure 3 shown.

[0083] from Figure 3 It can be seen that as the number of repetitions increases, the wettability of the membrane further increases. When the number of repetitions is 10, the membrane water contact angle is 30 degrees and the wetting time is 0.23 seconds, indicating that the composite membrane modified with hydrotalcite has super hydrophilicity. This improvement in hydrophilicity can effectively inhibit the precipitation of bubbles on the membrane surface, thereby reducing the ohmic loss caused by bubbles and improving the water electrolysis efficiency.

[0084] Test Example 3

[0085] In this test example, the electrolysis performance of commercial diaphragms (purchased from Tianjin Ruisibai Technology Co., Ltd.) and the composite diaphragms prepared in Example 1 were tested. The results are as follows: Figure 4 shown.

[0086] The alkaline water electrolysis experiment was carried out in a double-chamber zero-gap electrolyzer purchased from Maxi New Energy Technology Co., Ltd., model LSCF-261000, with an effective electrode area of ​​15 cm 2 The diaphragm was replaced with this product, 30% KOH was used as the electrolyte, and the tank temperature was controlled at 80°C. A DC power supply was used for power supply, and the current density range was 0A / m 2Up to 10000A / m 2 , step length 1000A / m 2 , record the corresponding voltage. Figure 4 It can be seen that based on the super hydrophilicity of the hydrotalcite-modified composite membrane and the catalytic effect of the NiFe hydrotalcite-modified composite membrane, the composite membrane of Example 1 is superior to the commercial membrane in water electrolysis performance, and the current density reaches 5000A / m at a cell voltage of 2V. 2 (Commercial diaphragm UTP 500: Current density reaches nearly 3000A / m at a cell voltage of 2V 2 ).

[0087] Test Example 4

[0088] In this test, the average pore size, alkali absorption rate, surface resistance, porosity, water contact angle and wetting time of the diaphragms of the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 2 were measured. The measurement results are shown in Table 1.

[0089] The average pore size can reflect the pore size of the membrane and the OH - Permeability and gas barrier properties are of great significance. The test method refers to GBT 21650.1-2008 "Determination of pore size distribution and porosity of solid materials by mercury injection and gas adsorption".

[0090] The surface resistance of the diaphragm has an important influence on the conductivity of the diaphragm. The surface resistance refers to the resistance value per unit area of ​​the diaphragm, which indicates the resistance of current passing through the diaphragm. The lower the surface resistance, the smaller the resistance value per unit area, and the smaller the resistance when current passes through the diaphragm. The test method refers to SJT10171.5-1991 "Test Method for Performance of Alkaline Battery Diaphragm".

[0091] Porosity is directly related to the conductivity of the membrane. A larger porosity means a larger electrolyte flux and a smaller surface resistance of the membrane. In this test example, the composite membrane was cut into 2cm×2cm squares, the dry weight was measured, and then immersed in deionized water for 12 hours; then the porosity of the composite membrane was calculated by measuring the mass and volume difference between the dry membrane and the wet membrane before and after water absorption.

[0092] Bubble point pressure refers to the pressure at which the gas in the diaphragm begins to penetrate at a certain temperature. A higher bubble point pressure indicates that the diaphragm has better gas barrier properties and can more effectively prevent gas penetration. The test method refers to GB / T26204-2010 "Performance Test Method of Liquid Phase Filter Materials - Air Bubble Point Test".

[0093] The water contact angle can reflect the wetting properties of the film. The test method refers to GB / T30693-2014 "Measurement of the contact angle between plastic film and water". The wetting time is the time difference from when the water droplet contacts the diaphragm and begins to generate a contact angle until the contact angle reaches 0 degrees.

[0094] After gradient construction of the nickel-iron hydrotalcite hydrophilic composite layer, the porosity is ≤60% and the bubble point pressure is ≥2 bar, indicating that the pore filling strategy can effectively fill the macropores locally, making the diaphragm have better gas barrier properties. Due to the increase in surface roughness, the diaphragm has superhydrophilicity. This superhydrophilicity greatly improves the performance of the diaphragm in the water electrolysis process and reduces the energy consumption of the system.

[0095] Table 1

[0096]

[0097]

[0098] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0099] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm, characterized in that: include: A substrate, the surface of which is formed with an array of bulk hydrotalcite-like structures, and nano flower ball structures are grown on the edges of the hydrotalcite-like structures.

2. The super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The hydrotalcite-like structure includes nickel-iron bimetallic layered hydroxide, and the hydrotalcite-like structure fills the pores of the substrate.

3. The super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The substrate comprises one or more of polyphenylene sulfide fabric, polyphenylene sulfide non-woven fabric, and an inorganic-organic composite substrate containing nano-ceramic filler.

4. A method for preparing a super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm, comprising: A substrate is sequentially immersed in a nickel-iron bimetallic salt solution and a potassium hydroxide solution; Rinse the surface of the substrate and dry it naturally; And drying to obtain the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm.

5. The method for preparing the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 4, characterized in that: The nickel-iron bimetallic salt solution includes one or more of nitrates and sulfates of nickel metal and one or more of nitrates and sulfates of iron metal.

6. The method for preparing the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 5, characterized in that: The molar ratio of Ni to Fe in the nickel-iron bimetallic salt solution is 1:(0.5 to 2).

7. The method for preparing the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 4, characterized in that: The immersion step and the rinsing and air-drying step are repeated 1 to 15 times in sequence.

8. The method for preparing the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 4, characterized in that: The time of immersion in the nickel-iron bimetallic salt solution is 1 min to 10 min, and the time of immersion in the potassium hydroxide solution is 1 min to 10 min.

9. The method for preparing the super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 4, characterized in that: The drying temperature is 60°C to 100°C.

10. An electrochemical energy device, characterized in that: include: The super-hydrophilic hydrotalcite-modified alkaline water electrolysis composite diaphragm according to claim 1 is used as the diaphragm.

11. The electrochemical energy device according to claim 10, characterized in that: It is a device for producing hydrogen by electrolyzing water.

Citation Information

Patent Citations

  • Hydrophilic modification method of diaphragm for electrolyzed water, hydrophilic diaphragm and application

    CN114351186A

  • High-hydrophilicity alkaline electrolyzed water diaphragm and preparation method thereof

    CN116334690A

  • Water electrolysis hydrogen production super-hydrophilic diaphragm and preparation method thereof

    CN117089887A